EVANS SYNDROME IN A 10 YEAR OLD GIRL - Ariputra, A. (Medicina, 2015)
Evans syndrome is a coexistence of simultaneous or sequential positive direct Coombs test in conjunctionwith  immune-mediated  thrombocytopenia with no known underlying etiology. The  clinical  course  ischronic and relapsing, and the therapy is generally progressive. Recurrences of thrombocytopenia, anemiaand neutropenia are common, as well as episodes of hemorrhage and serious infections. Noncrossreactingautoantibodies are directed against red cells, platelets, and neutrophils antigens. Evans syndrome isa rare condition, no predilection is known and its exact prevalent is unknown. We report a case of Evanssyndrome in 10 years old girl with severe anemia and thrombocytopenia. Patient came with clinicalsymptoms of severe anemia. The laboratory evaluation showed severe anemia, increased reticulocytecount, anisopoikilocytosis erythrocyte, increased unconjugated bilirubin, positive direct Coombs testand thrombocytopenia. Patient was then managed with high doses of corticosteroids and showed goodresponse from both clinical and laboratory evaluations. [MEDICINA 2015;46:61-66]. Sindrom Evans adalah suatu penyakit yang ditandai dengan adanya hasil positif pada direct Coombstest dan trombositopenia yang diperantarai  imun secara simultan atau sekuensial tanpa penyebabyang  jelas. Perjalanan klinis umumnya bersifat kronis, sering mengalami relaps dan memerlukanterapi yang progresif. Kejadian trombositopenia, anemia, neutropenia, perdarahan dan episode infeksiberat berulang umum terjadi. Pada sindrom ini, terjadi reaksi autoantibodi spesifik terhadap antigensel darah merah, trombosit dan juga neutrofil. Sindrom Evans merupakan kasus yang jarang ditemukandan dengan predileksi serta prevalensi yang belum banyak diketahui. Kami melaporkan satu kasusSindrom Evans pada anak perempuan usia 10 tahun.  Pasien dengan gejala klinis anemia berat dan padapemeriksaan laboratorium menunjukkan suatu anemia berat, peningkatan hitung retikulosit, gambaraneritrosit anisopoikilositosis, peningkatan kadar bilirubin yang tidak terkonjugasi, direct Coombs test yangpositif  dan  trombositopenia.  Pasien  kemudian  diterapi  dengan  kortikosteroid  dosis  tinggi  dandidapatkan respon yang baik pada evaluasi klinis dan laboratorium. [MEDICINA 2015;46:61-66].
Keywords: Evans syndrome, anemia, thrombocytopenia